PEMBATASAN TERHADAP HAK ASASI MANUSIA DALAM PRESPEKTIF KEADAAN DARURAT - Osgar S Matompo (Jurnal Media Hukum, 2014)
Human  rights  is a gift  from Allah SWT, as a consequence becoming human  creature, therefore  it couldn’t be deprived  or  abolished  by  the  state.  If  a  state  in  an  abnormal  condition  or  emergency  condition,  state  is allowed  to  take an extraordinary action  including giving restriction  to human  right  for  the  sake of defending state  integrity  and  protect  its  citizens, but  human  right  that  could  be  restricted  is  human  right which  is categorized  in  non-derogable  right  (right  that  couldn’t  be  limited  in  any  kind of  condition).  This  research found  that  in  the practice of human  right restriction which  is applied  in any kind of emergency condition  in various area of  Indonesia precisely  touch  the  rights which are non-derogable  rights.